2010
DOI: 10.1128/iai.00698-10
|View full text |Cite
|
Sign up to set email alerts
|

In VitroCharacterization of the Microglial Inflammatory Response toStreptococcus suis, an Important Emerging Zoonotic Agent of Meningitis

Abstract: Streptococcus suis is an important swine and human pathogen responsible for septicemia and meningitis. In vivo research in mice suggested that in the brain, microglia might be involved in activating the inflammatory response against S. suis. The aim of this study was to better understand the interactions between S. suis and microglia. Murine microglial cells were infected with a virulent wild-type strain of S. suis. Two isogenic mutants deficient at either capsular polysaccharide (CPS) or hemolysin production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 73 publications
4
49
0
Order By: Relevance
“…To study this objective, we used a CPS Ϫ mutant of S. suis and compared it with its WT encapsulated strain. In previous studies, using quantitative techniques combined with confocal and electron microscopy, we demonstrated that wellencapsulated S. suis is poorly phagocytosed by macrophages, whereas nonencapsulated strains are rapidly ingested and killed by most phagocytes, including J774 macrophages (5,14,27,28,35). First, S. suis was allowed to interact with cells for either 30 min or 1 h, and then lipid microdomains were labeled with cholera toxin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To study this objective, we used a CPS Ϫ mutant of S. suis and compared it with its WT encapsulated strain. In previous studies, using quantitative techniques combined with confocal and electron microscopy, we demonstrated that wellencapsulated S. suis is poorly phagocytosed by macrophages, whereas nonencapsulated strains are rapidly ingested and killed by most phagocytes, including J774 macrophages (5,14,27,28,35). First, S. suis was allowed to interact with cells for either 30 min or 1 h, and then lipid microdomains were labeled with cholera toxin.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, type 2 CPS plays a key role by protecting the pathogen against phagocytosis and by preventing bacterial surface antigen recognition by immune cell receptors (2,14,20,37,41). Surface polysaccharides can also display similarities to host antigens and are often poorly immunogenic (26,39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on meningitis-associated bacteria have shown that a fatal disease outcome can be caused by the host inflammatory response (Dominguez-Punaro et al 2007). Dominguez-Punaro et al (2010) showed that after being stimulated by an SS CPS-deficient mutant, the microglia induced significantly higher levels of proinflammatory mediators than that of the wild-type strain. Here, our results suggest that SS increases CPS as a protective mechanism against phagocytosis and killing in blood and reduces expression of CPS in CSF to expose the cell wall components, thereby facilitating a higher inflammatory response in the brain.…”
Section: Discussionmentioning
confidence: 99%